Whole Transcriptome Analysis Provides Insights Into the Molecular Mechanisms of Chlamydospore-Like Cell Formation in Phanerochaete chrysosporium - Liu, Lei; Li, Huihui; Liu, Yanyan; Li, Yi; Wang, Hailei (Frontiers in Microbiology, 2020)
Phanerochaete chrysosporium is a white rot fungus naturally isolated from hardwoods and widely used in environmental pollution control because it produces extracellular peroxidases. It forms chlamydospores during nitrogen starvation, which naturally occurs in the habitat of P. chrysosporium. Chlamydospores protect fungi against many stresses, the molecular basis underlying chlamydospore formation in basidiomycetes is poorly explored. Chlamydospores in P. chrysosoporium have a different cell wall compared with hyphae, as confirmed by cell wall digestion and microscopy. Furthermore, this study investigated the transcriptome of P. chrysosporium in different life stages, including conidium, hypha, and chlamydospore formation, through RNA sequencing. A total of 2215 differentially expressed genes were identified during these processes. The expression patterns of genes involved in several molecular events critical for chlamydospore formation, including starch and sucrose metabolism, phosphatase and kinase, and transcription factors, were determined. This study serves as a basis for further investigating the function of chlamydospore formation in the biotechnologically relevant fungus P. chrysosporium.